High-voltage vacuum insulating part material and preparation method thereof
By modifying the hyperbranched polymer molecular chain on the surface of mullite fibers, preparing modified fiber materials, and mixing them with PA66 and other materials, the problem of insufficient mechanical and mechanical properties of PA66-based high-pressure vacuum insulating parts is solved, and the performance improvement of the material is achieved and sustainable development.
Patent Information
- Application Number
- CN202411648794.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The mechanical and mechanical properties of the existing PA66-based high-voltage vacuum insulator materials cannot meet the high-performance requirements, and the interface problems after adding inorganic nanomaterials lead to a decline in material performance.
Modified fibers are prepared by modifying the hyperbranched polymer molecular chains on the surface of mullite fibers and mixing them with PA66, antioxidant additives, lubricants and filler additives to prepare high-pressure vacuum insulation by extrusion granulation process Material.
It improves the mechanical and mechanical properties of PA66, enhances the breakdown strength and volume resistivity of the material, solves the problem of separation of materials during use, and improves the overall performance of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a high-voltage vacuum insulation material and a preparation method thereof. Background Art
[0002] With the rapid development of the electric power industry, high-voltage vacuum equipment is increasingly used in power systems. In these devices, the performance of the insulation material is directly related to the operating stability and safety of the equipment. Therefore, the selection of high-performance insulation materials is crucial to improving the overall performance of the equipment. At present, epoxy resin has excellent electrical properties, extremely high insulation strength, low dielectric constant and dielectric loss, and can meet the high-performance requirements of high-voltage vacuum equipment for insulation. Therefore, it is widely used in vacuum high-voltage insulation materials. However, epoxy resin casting materials are thermosetting materials, which will cause great pollution to the environment after being discarded. Relatively speaking, polyamide 66 (PA66) has lower costs, and waste can be recycled and reused. It also has a lower dielectric constant and dielectric loss, and can show excellent electrical properties. Therefore, using PA66 as an alternative to epoxy resin is of great significance for the sustainable development of high-voltage vacuum insulation materials.
[0003] However, the mechanical properties of PA66 cannot meet the requirements of high-performance high-voltage vacuum insulation materials, so there are still deficiencies in practical applications. At present, there are many studies on improving the mechanical properties of PA66 by adding inorganic nanomaterials, and there are related reports, but most of them only stay at the stage of physically blending the two, without considering the interface problems between them, which may cause the materials to separate from each other during use, resulting in a sharp decline in material performance. Based on this, the present invention provides a PA66-based high-voltage vacuum insulation material with excellent mechanical properties, which can solve the above technical problems. Summary of the invention
[0004] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a high-voltage vacuum insulation material and a preparation method thereof.
[0005] (II) Technical solution A method for preparing a high-voltage vacuum insulation material, the vacuum insulation material comprising the following raw materials in parts by weight: PA66 75-85 parts; 4-8 parts of modified fiber material; 0.1-0.5 parts of antioxidant additives; Lubricant 0.5-1 part; 5-12 parts of filling additives; The preparation method comprises the following steps: S1. Ingredients Weigh each raw material in parts by weight and set aside; S2. Extrusion granulation Put PA66, modified fiber material, antioxidant additive, lubricant and filling additive into a high-speed mixer, stir and mix at a stirring rate of 1000-2000r / min, then feed the mixture into an extruder through a feeding port, control the temperature of each section of the extruder to 250-260℃, 260-270℃, 260-270℃, 270-280℃, 260-270℃, 260-270℃, 250-260℃, 240-250℃, 250-260℃, control the screw speed to 200-300r / min, carry out melt extrusion operation, collect masterbatch, and obtain insulating material.
[0006] Further preferably, the preparation method of the modified fiber material is as follows: S10, Surface modification The mullite fiber is ultrasonically dispersed in a dimethyl sulfoxide solvent to form a uniform dispersion, and then 2,2-bis(4-glycidyl ether)phenyl)adamantane is added to the dispersion under nitrogen protection, and a metal tin catalyst is added at the same time. After the addition, a heating program is started, the temperature is controlled at 130-150°C, stirring is continued for 3-6 hours, the temperature is lowered and the material is discharged, and the product is collected to obtain a modified mullite fiber; S20, hyperbranched modification The modified mullite fiber is mixed with toluene, and then ultrasonically dispersed until a uniform dispersion is formed, and then a hyperbranched bridging agent and a phase transfer catalyst are added to the dispersion, and nitrogen is introduced to exhaust the air, and then the temperature is maintained at 60-70°C. After keeping warm for 2-4 hours, 2,2-bis(4-glycidylether)phenyl)adamantane is continuously added to the dispersion. After the addition is completed, stirring is continued for 9-12 hours, the temperature is lowered and the material is discharged, and the solid material is separated and collected to obtain a modified fiber material.
[0007] Further preferably, in step S10, the length of the mullite fiber is 1-2 mm.
[0008] Further preferably, in step S10, the metal tin catalyst is stannous chloride.
[0009] More preferably, in step S20, the hyperbranched bridging agent is one or more of trisaccharide, 1,3,5-pentanetricarboxylic acid or 1,2,4-butanetricarboxylic acid.
[0010] Further preferably, in step S20, the phase transfer catalyst is one or more of tetrabutylammonium bromide, tetramethylammonium bromide, tetrabutylammonium hydrogen sulfate or tetrabutylammonium chloride.
[0011] In step S10, under the action of a metal tin catalyst, the epoxy groups in the structure of 2,2-bis(4-glycidyl ether)phenyl)adamantane can interact with the silanol groups on the surface of the mullite fiber to open the ring, thereby modifying the surface of the mullite fiber with 2,2-bis(4-glycidyl ether)phenyl)adamantane to obtain a modified mullite fiber. Then, the epoxy groups of the modified mullite fiber are further bridged with a hyperbranched bridging agent, and by adding 2,2-bis(4-glycidyl ether)phenyl)adamantane, under the action of a phase transfer catalyst, the hyperbranched bridging agent and 2,2-bis(4-glycidyl ether)phenyl)adamantane are continuously and uninterruptedly subjected to a ring-opening esterification reaction on the surface of the mullite fiber to obtain a mullite fiber whose surface is modified with a hyperbranched polymer molecular chain, i.e., a modified fiber material.
[0012] Further preferably, the antioxidant aid is a combination of lignin and antioxidant 168, with a mass ratio of 1:0.1-0.2.
[0013] Further preferably, the lubricant is one or more of zinc stearate, calcium stearate or polyethylene wax.
[0014] More preferably, the filling aid is one or more of fumed silica, titanium dioxide, talc or calcium carbonate.
[0015] A high-voltage vacuum insulation material is prepared by adopting the preparation method.
[0016] 3. Beneficial technical effects The present invention obtains modified fiber material by modifying hyperbranched polymer molecular chain on the surface of mullite fiber. First, the hyperbranched molecular chain structure contains hydroxyl groups produced by ring-opening reaction, so it can produce hydrogen bonding with PA66 molecular chain in melting process, and then produce mutual entanglement with PA66 molecular chain, and extend into each region of PA66 matrix, forming a micro three-dimensional network structure interwoven with each other, so that mullite fiber can efficiently play the role of transferring load, and enhance the mechanical properties of PA66. Secondly, the hyperbranched molecular chain on the surface of mullite fiber contains rigid chain link, which makes up for the deficiency of PA66 as straight chain molecule, and further improves its mechanical properties. In addition, after the surface is modified by hyperbranched polymer molecular chain, mullite fiber can be mutually dispersed in PA66 matrix in a disordered state due to the existence of steric effect, and then can produce a larger scattering effect to electrons, improve the volume resistivity of the material, so that it shows higher breakdown strength. DETAILED DESCRIPTION
[0017] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] The PA66 used in the examples and comparative examples of the present invention was purchased from Henan Shenma Huawei Plastic Co., Ltd., model EPR2701; fumed silica was purchased from fumed silica (H15), industrial grade, purchased from Wacker Chemie (China) Co., Ltd.; titanium dioxide was purchased from Jinan Quanhui Chemical Co., Ltd.; other undisclosed reagents were commercially available.
[0019] Embodiment 1: A high voltage vacuum insulation material, comprising the following raw materials in parts by weight: PA66 75 parts; 4 parts of modified fiber material; 0.1 part of antioxidant additive; 0.5 parts of zinc stearate; 5 parts of fumed silica; The method for preparing the high voltage vacuum insulation material comprises the following steps: S1. Ingredients Weigh each raw material in parts by weight and set aside; S2. Extrusion granulation Put PA66, modified fiber material, antioxidant, lubricant and filling additive into a high-speed mixer, stir and mix at a stirring rate of 1000r / min, then feed the mixture into the extruder through the feeding port, control the temperature of each section of the extruder to 250℃, 260℃, 260℃, 270℃, 260℃, 260℃, 250℃, 240℃, 250℃, and control the screw speed to 200r / min, carry out melt extrusion operation, collect the masterbatch, and then the insulating material can be obtained.
[0020] The antioxidant aid is a combination of lignin and antioxidant 168, with a mass ratio of 1:0.1; Wherein, the preparation method of the modified fiber material is as follows: S10, Surface modification 3 g of mullite fiber with a length of 1 mm was ultrasonically dispersed in a dimethyl sulfoxide solvent to form a uniform dispersion, and then 6.5 g of 2,2-bis(4-glycidylether)phenyl)adamantane was added to the dispersion under nitrogen protection, and 0.1 g of stannous chloride was added at the same time. After the addition, the heating program was turned on, the temperature was controlled at 140°C, and the stirring was continued for 4 hours. The material was discharged after cooling, and the product was collected to obtain the modified mullite fiber; S20, hyperbranched modification 4.5 g of modified mullite fiber was mixed with toluene, and then ultrasonically dispersed until a uniform dispersion was formed. Then, 12 g of triacylglycerol and 0.5 g of tetrabutylammonium bromide were added to the dispersion, and nitrogen was introduced to exhaust the air. Then, the temperature was maintained at 65°C. After keeping the temperature for 3 hours, 6.5 g of 2,2-bis(4-glycidylether)phenyl)adamantane was added to the dispersion. After the addition was completed, stirring was continued for 12 hours, the temperature was lowered and the material was discharged. The solid material was separated and collected to obtain the modified fiber material.
[0021] Embodiment 2: A high voltage vacuum insulation material, comprising the following raw materials in parts by weight: PA66 80 parts; 6.5 parts of modified fiber material; 0.2 parts of antioxidant additives; 0.6 parts of zinc stearate; 10 parts of fumed silica; The method for preparing the high voltage vacuum insulation material comprises the following steps: S1. Ingredients Weigh each raw material in parts by weight and set aside; S2. Extrusion granulation Put PA66, modified fiber material, antioxidant, lubricant and filling agent into a high-speed mixer, stir and mix at a stirring rate of 1500r / min, then feed the mixture into the extruder through the feeding port, control the temperature of each section of the extruder to 255°C, 265°C, 265°C, 275°C, 265°C, 265°C, 255°C, 245°C, and 255°C in sequence, and control the screw speed to 300r / min, carry out melt extrusion operation, collect masterbatch, and obtain insulating material.
[0022] The antioxidant aid is a combination of lignin and antioxidant 168, with a mass ratio of 1:0.2; The preparation method of the modified fiber material is the same as that in Example 1.
[0023] Embodiment 3: A high voltage vacuum insulation material, comprising the following raw materials in parts by weight: PA66 85 parts; 8 parts of modified fiber material; 0.5 parts of antioxidant additives; 1 part of calcium stearate; Titanium dioxide 12 parts; The method for preparing the high voltage vacuum insulation material comprises the following steps: S1. Ingredients Weigh each raw material in parts by weight and set aside; S2. Extrusion granulation Put PA66, modified fiber material, antioxidant additive, calcium stearate and titanium dioxide into a high-speed mixer, stir and mix at a stirring rate of 2000r / min, then feed the mixture into the extruder through the feeding port, control the temperature of each section of the extruder to 260℃, 270℃, 270℃, 280℃, 270℃, 270℃, 260℃, 250℃, 260℃, and control the screw speed to 300r / min, carry out melt extrusion operation, collect the masterbatch, and then the insulating material can be obtained.
[0024] The antioxidant aid is a combination of lignin and antioxidant 168, with a mass ratio of 1:0.2; The preparation method of the modified fiber material is the same as that in Example 1.
[0025] Comparative Example 1: A high-voltage vacuum insulation material, comprising the following raw materials in parts by weight: PA66 80 parts; Mullite fiber 6.5 parts; 0.2 parts of antioxidant additives; 0.6 parts of zinc stearate; 10 parts of fumed silica; The method for preparing the high voltage vacuum insulation material comprises the following steps: S1. Ingredients Weigh each raw material in parts by weight and set aside; S2. Extrusion granulation Put PA66, mullite fiber, antioxidant, lubricant and filling agent into a high-speed mixer, stir and mix at a stirring rate of 1500r / min, then feed the mixture into the extruder through the feeding port, control the temperature of each section of the extruder to 255°C, 265°C, 265°C, 275°C, 265°C, 265°C, 255°C, 245°C, and 255°C in sequence, and control the screw speed to 300r / min, carry out melt extrusion operation, collect masterbatch, and obtain insulating material.
[0026] The antioxidant aid is a composition of lignin and antioxidant 168, with a mass ratio of 1:0.2.
[0027] Comparative Example 2: A high-voltage vacuum insulation material, comprising the following raw materials in parts by weight: PA66 80 parts; 0.2 parts of antioxidant additives; 0.6 parts of zinc stearate; 10 parts of fumed silica; The method for preparing the high voltage vacuum insulation material comprises the following steps: S1. Ingredients Weigh each raw material in parts by weight and set aside; S2. Extrusion granulation Put PA66, antioxidant, lubricant and filling agent into a high-speed mixer, stir and mix at a stirring rate of 1500r / min, then feed the mixture into the extruder through the feeding port, control the temperature of each section of the extruder to 255°C, 265°C, 265°C, 275°C, 265°C, 265°C, 255°C, 245°C, and 255°C in sequence, and control the screw speed to 300r / min, carry out melt extrusion operation, collect the masterbatch, and then the insulating material can be obtained.
[0028] The antioxidant aid is a composition of lignin and antioxidant 168, with a mass ratio of 1:0.2.
[0029] Test Case The materials in Examples 1 to 3 and Comparative Examples 1 to 2 were injection molded into samples that met various test specifications, and various tests were performed; According to the standard GB / T 1040.2-2008, the tensile properties were tested at a rate of 5 mm / min; According to standard GB / T 9341-2008, test the bending strength; According to standard GB / T 1043.1-2008, test the impact strength; According to the standard GB / T 1408.1-2006, the breakdown strength test is carried out; The test results are as follows:
[0030] The analysis results show that the materials prepared using modified fiber materials as additives have significantly better mechanical and other properties. After the modified fiber materials are replaced with mullite fibers without surface modification, the performance has dropped significantly. On the one hand, it may be due to the slight agglomeration of mullite fibers, which affects its own reinforcement effect. On the other hand, it is due to the loss of the reinforcement effect of the rigid chain links. After removing the mullite fibers, the performance declines more significantly, indicating that the addition of mullite fibers has a reinforcing effect on PA66.
[0031] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.
Claims
1. A method for preparing a high voltage vacuum insulation material, characterized in that: The vacuum insulation material comprises the following raw materials in parts by weight: PA66 75-85 parts; 4-8 parts of modified fiber material; 0.1-0.5 parts of antioxidant additives; Lubricant 0.5-1 part; 5-12 parts of filling additives; The preparation method comprises the following steps: S1. Ingredients Weigh each raw material in parts by weight and set aside; S2. Extrusion granulation Put PA66, modified fiber material, antioxidant additive, lubricant and filling additive into a high-speed mixer, stir and mix at a stirring rate of 1000-2000r / min, then feed the mixture into an extruder through a feeding port, control the temperature of each section of the extruder to 250-260℃, 260-270℃, 260-270℃, 270-280℃, 260-270℃, 260-270℃, 250-260℃, 240-250℃, 250-260℃, and control the screw speed to 200-300r / min, perform melt extrusion operation, collect masterbatch, and obtain insulating material; The preparation method of the modified fiber material is as follows: S10, Surface modification The mullite fiber is ultrasonically dispersed in a dimethyl sulfoxide solvent to form a uniform dispersion, and then 2,2-bis(4-glycidyl ether)phenyl)adamantane is added to the dispersion under nitrogen protection, and a metal tin catalyst is added at the same time. After the addition, a heating program is started, the temperature is controlled at 130-150°C, stirring is continued for 3-6 hours, the temperature is lowered and the material is discharged, and the product is collected to obtain a modified mullite fiber; S20, hyperbranched modification The modified mullite fiber is mixed with toluene, and then ultrasonically dispersed until a uniform dispersion is formed, and then a hyperbranched bridging agent and a phase transfer catalyst are added to the dispersion, and nitrogen is introduced to exhaust the air, and then the temperature is maintained at 60-70°C. After heat preservation for 2-4 hours, 2,2-bis(4-glycidylether)phenyl)adamantane is continuously added to the dispersion, and after the addition is completed, stirring is continued for 9-12 hours, the temperature is lowered and the material is discharged, and the solid material is separated and collected to obtain a modified fiber material; In the step S20, the hyperbranched bridging agent is one or more of trisaccharide, 1,3,5-pentanetricarboxylic acid, and 1,2,4-butanetricarboxylic acid.
2. The method for preparing a high voltage vacuum insulation material according to claim 1, characterized in that: In the step S10, the length of the mullite fiber is 1-2 mm.
3. The method for preparing a high voltage vacuum insulation material according to claim 1, characterized in that: In the step S10, the metal tin catalyst is stannous chloride.
4. The method for preparing a high voltage vacuum insulation material according to claim 1, characterized in that: In step S20, the phase transfer catalyst is one or more of tetrabutylammonium bromide, tetramethylammonium bromide, tetrabutylammonium hydrogen sulfate or tetrabutylammonium chloride.
5. The method for preparing a high voltage vacuum insulation material according to claim 1, characterized in that: The antioxidant aid is a composition of lignin and antioxidant 168, with a mass ratio of 1:0.1-0.
2.
6. The method for preparing a high voltage vacuum insulation material according to claim 1, characterized in that: The lubricant is one or more of zinc stearate, calcium stearate or polyethylene wax.
7. The method for preparing a high voltage vacuum insulation material according to claim 1, characterized in that: The filling auxiliary agent is one or more of fumed silica, titanium dioxide, talcum powder or calcium carbonate.
8. A high voltage vacuum insulation material, characterized in that: The method is prepared according to any one of claims 1 to 7.
Citation Information
Patent Citations
Polyamide-based insulation composite material with low linear expansion coefficient and high thermal conductivity and preparation method thereof
CN108624039A
High-breakdown-voltage-resistant glass fiber reinforced flame-retardant composite material and preparation method thereof
CN114213839A
Preparation method of carbon fiber composite material and application of carbon fiber composite material in scooter
CN118725554A
Thermoplastic polymer composition with hyperbranched polymer and products made with the composition
JP2005513186A